The ordering of senses in English-Xitsonga bilingual dictionaries : Towards logical meaning arrangement in the microstructure - Machimana, Abios Sparks (University of Limpopo (Turfloop Campus), 2009)
In many bilingual dictionaries, translation equivalents reveal some shortcomings with regard to the manner in which they are presented, particularly the English-Xitsonga bilingual dictionaries. Translation equivalents in the microstructure are frequently arranged and are without contextual guidance to assist the user. This way of presentation impedes the dictionary users from retrieving the appropriate and accurate equivalents. The study has, therefore, evaluated the way in which these translation equivalents are arranged. This research study shows that they should be logically and systematically arranged, starting with the translation equivalents that have the highest usage frequency to be user-friendly. The study also suggests that functional equivalence must prevail in English-Xitsonga bilingual dictionaries. The problem of zero-equivalence should also be resolved by giving a comprehensive description of the lemma as a translation equivalent to help the users to understand the lemma better.
Thesis (M.A. (Linguistics)) --University of Limpopo, 2009
Keywords: Bilingual dictionaries; Translation; 420.802; Dictionaries, Polyglot -- South Africa; Translations -- South Africa